Natriuretic Hormones in Brain Function - Hodes, Anastasia; Lichtstein, David (Frontiers in Endocrinology, 2014)
Natriuretic hormones include three groups of compounds: the natriuretic peptides (ANP, BNP and CNP), the gastrointestinal peptides (guanylin and uroguanylin), and endogenous cardiac steroids. These substances induce the kidney to excrete sodium and therefore participate in the regulation of sodium and water homeostasis, blood volume and blood pressure. In addition to their peripheral functions, these hormones act as neurotransmitters or neuromodulators in the brain. In this review, the established information on the biosynthesis, release and function of natriuretic hormones is discussed, with particular focus on their role in brain function. The available literature on the expression patterns of each of the natriuretic hormones and their receptors in the brain will be summarized, followed by the evidence for their roles in modulating brain function. Although numerous open questions exist regarding this issue, the available data support the notion that natriuretic hormones participate in the central regulation of blood pressure, neuroprotection, satiety, and various psychiatric conditions, including: anxiety, addiction and depressive disorders. In addition, the interactions between the different natriuretic hormones in the periphery and the brain are discussed.